2013
DOI: 10.1161/hypertensionaha.113.01653
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Cardiotrophin 1 on Atherosclerosis

Abstract: A therosclerosis is a pathological injury-to-response process that is initiated by early inflammatory responses of vascular endothelial cells (ECs).1 Endothelial inflammation is characterized by increased production of proatherogenic molecules and inflammatory cytokines in ECs, and monocyte adhesion and infiltration into the neointima lesion, followed by oxidized low-density lipoprotein-induced transformation of macrophages into foam cells.2 Accumulation of cholesterol ester in macrophages is a hallmark of foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(112 citation statements)
references
References 48 publications
0
111
0
1
Order By: Relevance
“…In contrast, other studies observed that CT-1 increased TNF-a in human peripheral blood mononuclear cells [124] and stimulated monocyte adhesion and migration [125,126] suggesting a contribution to the inflammatory process [125]. In line with these studies, four-week infusion of rCT-1 into ApoE À/À significantly accelerated the development of aortic atherosclerotic lesions [127]. Ló pez-Andres et al reported that chronic exposure of rCT-1 for six weeks was associated with cardiac, vascular and renal fibrosis resulting in further structural and functional damage [35].…”
Section: Inflammationmentioning
confidence: 73%
“…In contrast, other studies observed that CT-1 increased TNF-a in human peripheral blood mononuclear cells [124] and stimulated monocyte adhesion and migration [125,126] suggesting a contribution to the inflammatory process [125]. In line with these studies, four-week infusion of rCT-1 into ApoE À/À significantly accelerated the development of aortic atherosclerotic lesions [127]. Ló pez-Andres et al reported that chronic exposure of rCT-1 for six weeks was associated with cardiac, vascular and renal fibrosis resulting in further structural and functional damage [35].…”
Section: Inflammationmentioning
confidence: 73%
“…There are evidence that CT-1 plasma levels can be elevated in patients with hypertension [20], coronary artery disease [21,22], and heart failure [23]. A recent experimental study indicated that CT-1 accelerates the development of atherosclerotic lesions by stimulating the inflammasome, foam cell formation associated with CD36 and acyl-CoA: cholesterol acyltransferase-1 upregulation in macrophages, and migration, proliferation, and collagen-1 production in vascular smooth muscle cells [24]. Our study provided new information on increased CT-1 among persistent AF patients without structural heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory response to injury of the arterial wall . Endothelial inflammation stimulates the production of proatherogenic adhesion molecules, such as tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), monocyte chemotactic protein‐1 (MCP‐1), intercellular adhesion molecule‐1 (ICAM‐1), vascular adhesion molecule‐1 (VCAM‐1), and E‐selectin in endothelial cells (ECs).…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory response to injury of the arterial wall. 19 Endothelial inflammation stimulates the production of proatherogenic adhesion molecules, such as tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6), monocyte chemotactic protein-1 (MCP-1), intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1 (VCAM-1), and E-selectin in endothelial cells (ECs). These effectors encourage monocyte adhesion and infiltration into the intimal layer, followed by fatty streak formation that is attributed to an accumulation of lipid-laden macrophage foam cells.…”
mentioning
confidence: 99%